Mobile applications using augmented reality to support older people - Abd Malik, Sofianiza; Abdullah, Lili Marziana; Mahmud, Murni; Azuddin, Muna (2013)
Increasing trends in using augmented reality applications on mobile devices among older people have been observed. It is well recognized that some problems are faced by older people in adopting mobile devices. It is vital to understand the problems in order to design better mobile devices that suit older people since they will make up the highest proportion of the population in later years. The paper highlights literatures conducted in investigating mobile applications and augmented reality applications developed for older people that can enhance the mobile device usage among them. The new trends of augmented reality applications allow older people to achieve more benefits from use of mobile devices.